Comparison of endoscopic endonasal and bifrontal craniotomy approaches for olfactory groove meningiomas: A matched pair analysis of outcomes and frontal lobe changes on MRI. Issue 11 (November 2015) - de Almeida, John R.; Carvalho, Felipe; Vaz Guimaraes Filho, Francisco; Kiehl, Tim-Rasmus; Koutourousiou, Maria; Su, Shirley; Vescan, Allan D.; Witterick, Ian J.; Zadeh, Gelareh; Wang, Eric W.; Fernandez-Miranda, Juan C.; Gardner, Paul A.; et al.
Abstract We compare the outcomes and postoperative MRI changes of endoscopic endonasal (EEA) and bifrontal craniotomy (BFC) approaches for olfactory groove meningiomas (OGM). All patients who underwent either BFC or EEA for OGM were eligible. Matched pairs were created by matching tumor volumes of an EEA patient with a BFC patient, and matching the timing of the postoperative scans. The tumor dimensions, peritumoral edema, resectability issues, and frontal lobe changes were recorded based on preoperative and postoperative MRI. Postoperative fluid-attenuated inversion recovery (FLAIR) hyperintensity and residual cystic cavity (porencephalic cave) volume were compared using univariable and multivariable analyses. From a total of 70 patients (46 EEA, 24 BFC), 10 matched pairs (20 patients) were created. Three patients (30%) in the EEA group and two (20%) in the BFC had postoperative cerebrospinal fluid leaks (p = 0.61). Gross total resections were achieved in seven (70%) of the EEA group and nine (90%) of the BFC group (p = 0.26), and one patient from each group developed a recurrence. On postoperative MRI, there was no significant difference in FLAIR signal volumes between EEA and BFC approaches (6.9 versus 13.3 cm3; p = 0.17) or in porencephalic cave volumes (1.7 versus 5.0 cm3; p = 0.11) in univariable analysis. However, in a multivariable analysis, EEA was associated with less postoperative FLAIR change (p = 0.02) after adjusting for the volume of preoperative edema. This study provides preliminary evidence that EEA is associated with quantifiable improvements in postoperative frontal lobe imaging.